Phase II trial of veliparib in patients with previously treated BRCA-mutated pancreas ductal adenocarcinoma. (January 2018) - Lowery, Maeve A.; Kelsen, David P.; Capanu, Marinela; Smith, Sloane C.; Lee, Jonathan W.; Stadler, Zsofia K.; Moore, Malcolm J.; Kindler, Hedy L.; Golan, Talia; Segal, Amiel; Maynard, Hannah; Hollywood, Ellen; et al.
Abstract: Purpose: BRCA-associated cancers have increased sensitivity to poly(ADP-ribose) polymerase inhibitors (PARPis). This single arm, non-randomised, multicentre phase II trial evaluated the response rate of veliparib in patients with previously treated BRCA1/2- or PALB2-mutant pancreatic adenocarcinoma (PDAC). Methods: Patients with stage III/IV PDAC and known germline BRCA1/2 or PALB2 mutation, 1–2 lines of treatment, Eastern Cooperative Oncology Group 0–2, were enrolled. Veliparib was dosed at a volume of 300 mg twice-daily (N = 3), then 400 mg twice-daily (N = 15) days 1–28. The primary end-point was to determine the response rate of veliparib; secondary end-points included progression-free survival (PFS), duration of response, overall survival (OS) and safety. Results: Sixteen patients were enrolled; male N = 8 (50%). Median age was 52 years (range 43–77). Five (31%) had a BRCA1 and 11 (69%) had a BRCA2 mutation. Fourteen (88%) patients had received prior platinum-based therapy. No confirmed partial responses (PRs) were seen: one (6%) unconfirmed PR was observed at 4 months with disease progression (PD) at 6 months; four (25%) had stable disease (SD), whereas 11 (69%) had PD as best response including one with clinical PD. Median PFS was 1.7 months (95% confidence interval [CI] 1.57–1.83) and median OS was 3.1 months (95% CI 1.9–4.1). Six (38%) patients had grade III toxicity, including fatigue (N = 3), haematology (N = 2) and nausea (N = 1). Conclusions: Veliparib was well tolerated, but no confirmed response was observed although four (25%) patients remained on study with SD for ≥ 4 months. Additional strategies in this population are needed, and ongoing trials are evaluating PARPis combined with chemotherapy (NCT01585805) and as a maintenance strategy (NCT02184195). Highlights: Veliparib has modest activity in previously treated germline BRCA-mutated pancreas cancer exposed to prior platinum therapy. Poly(ADP)-ribose) polymerase (PARP) inhibition in pancreas cancer may be best evaluated in a platinum-sensitive disease setting. There may be intrinsic differences between PARP inhibitors that explain therapeutic outcomes.